The influence of ethical leadership and organizational commitment on employee performance at PT. Masaji Tatanan Container Indonesia - Lestaluhu, Rakhmat Abdussalam; Pudjiati, Pudjiati; Muvano, Nandha Narendra (Institute of Computer Science (IOCS), 2023)
Ethical leadership is important in the current industrial development. It involves implementing good behaviors based on morals, setting a good example for employees, and having good value for the company. Ethical leadership is closely related to performance improvement. Additionally, organizational commitment also has a significant influence on performance. The decline in employee performance at PT MTKI is characterized by unachieved rental targets, one of which is due to the lack of enthusiasm for marketing products because employees are less adept at informing the facilities and facilities provided by the company. A study was conducted to determine the influence of ethical leadership and organizational commitment on employee performance at PT MTKI. Based on the research results, it is found that ethical leadership partially has a positive and significant effect on employee performance. Organizational commitment partially has a positive effect on employee performance. Organization partially has a positive effect on employee performance. The contribution of ethical leadership and organizational commitment to employee performance is 82% while the remaining 18% is influenced by other variables outside this study